2019
DOI: 10.21276/obgyn.2019.5.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of fetomaternal outcome using new screening criteria of serum TSH for diagnosing hypothyroidism in pregnancy

Abstract: Objectives: To assess the maternal and fetal outcomes using new screening criteria with upper serum thyroid stimulating hormone (TSH) cut off as >3mIU/L, for diagnosing hypothyroidism in pregnancy. Materials and Methods: This study was a cross sectional study, carried out in the department of Obstetrics and Gynaecology. During one year of study period from February 2016 to January 2017, pregnant women with ≤ 20 weeks gestation, attending antenatal OPD were included in the study and they were followed till deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The miscarriage rate in the study and control group was the same (p=0.1146). Similar findings were observed by Hiriyur et al, 17 and Joshi et al 18 As thyroid hormones have many effects on cardio-vascular physiology and blood pressure regulation, there is a high prevalence of gestational hypertension in hypothyroid women compared to euthyroid women. We observed 53 (33.125%) cases of pre-eclampsia in the study group compared to 13 (8.125%) cases in the control group.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The miscarriage rate in the study and control group was the same (p=0.1146). Similar findings were observed by Hiriyur et al, 17 and Joshi et al 18 As thyroid hormones have many effects on cardio-vascular physiology and blood pressure regulation, there is a high prevalence of gestational hypertension in hypothyroid women compared to euthyroid women. We observed 53 (33.125%) cases of pre-eclampsia in the study group compared to 13 (8.125%) cases in the control group.…”
Section: Discussionsupporting
confidence: 84%
“…Roy et al, also observed a high cesarean section rate in hypothyroid women and an increased rate of spontaneous vaginal delivery in euthyroid women. 1 Nevertheless, Hiriyur et al, 17 and Joshi et al, 18 found a similar cesarean section rate in both cases and control. A study done in Agha Khan showed that ladies with preconception TSH >2.5 µIU /ml had significantly high cesarean section rate.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations